A Patient-Centered Understanding of the Referral System in Ethiopian Primary Health Care Units - Abrahim, Orit (PLoS One, 2015)
BACKGROUND: Primary healthcare systems in sub-Saharan Africa have undergone substantial development in an effort to expand access to appropriate facilities through a well-functioning referral system. The objective of this study was to evaluate the current patterns of seeking prior care before arriving at a health center or a hospital as a key aspect of the referral system of the primary health care unit (PHCU) in three regions in Ethiopia. We examined what percentage of patients had either sought prior care or had been referred to the present facility and identified demographic and clinical factors associated with having sought prior care or having been referred. METHODS AND FINDINGS: We conducted a cross-sectional study using face-to-face interviews in the local language with 796 people (99% response rate) seeking outpatient care in three primary health care units serving approximately 100,000 people each and reflecting regional and ethnic diversity; 53% (N = 418) of the sample was seeking care at hospital outpatient departments, and 47% of the sample was seeking care at health centers (N = 378). We used unadjusted and adjusted logistic regression to identify factors associated with having been referred or sought prior care. Our findings indicated that only 10% of all patients interviewed had been referred to their current place of care. Among those in the hospital population, 14% had been referred; among those in the health center population, only 6% had been referred. Of those who had been referred to the hospital, most (74%) had been referred by a health center. Among those who were referred to the health center, the plurality portion (32%) came from a nearby hospital (most commonly for continued HIV treatment or early childhood vaccinations); only 18% had come from a health post. Among patients who had not been formally referred, an additional 25% in the hospital sample and 10% in the health center sample had accessed some prior source of care for their present health concern. In the adjusted analysis, living a longer distance from the source of care and needing more specialized care were correlated with having sought prior care in the hospital sample. We found no factors significantly associated with having sought prior care in the health center sample. CONCLUSIONS: The referral system among health facilities in Ethiopia is used by a minority of patients, suggesting that intended connections between health posts, health centers, and hospitals may need strengthening to increase the efficiency of primary care nationally.